Peacebuilding in Timor-Leste: United Nations missions and the post-intervention context. (1st June 2014) - Freire, Maria Raquel
This article looks at the process of intervention that took place in Timor-Leste particularly after the 1999 popular consultation where the majority of the voting was in favour of independence from Indonesian rule. Since then, the United Nations (UN) presence in Timor-Leste assumed different configurations, from the transitional administration to elections monitoring, including the use of force to contain violence. In the process of peace consolidation, the role of international interventionism was to assist the country in developing institutions and setting up processes for promoting good governance, aiming at stability-building. This article looks at the context where interventionism took place, particularly looking at the UN role until the end of the UN Integrated Mission in Timor-Leste (UNMIT) mandate in December 2012, seeking to shed light on the UN's contribution to peace. The article argues the UN's approach to peace has been mainly an institutional one, and that the challenges remaining and/or arising in the post-interventionist context are many regarding the consolidation of the state, both internally (structural approach to peace) and externally (projection of stability at the regional and international levels). Despite the remaining challenges, the article concludes with a positive assessment of the course of Timorese peace consolidation, and that the active foreign policy of Timor-Leste might constitute a building block in its internal consolidation process.